Encouraging Consumption of Water in School and Child Care Settings: Access, Challenges, and Strategies for Improvement - Patel, Anisha I. (American Public Health Association, 2011)
Children and adolescents are not consuming enough water, instead opting for sugar-sweetened beverages (sodas, sports and energy drinks, milks, coffees, and fruit-flavored drinks with added sugars), 100% fruit juice, and other beverages. Drinking sufficient amounts of water can lead to improved weight status, reduced dental caries, and improved cognition among children and adolescents. Because children spend most of their day at school and in child care, ensuring that safe, potable drinking water is available in these settings is a fundamental public health measure. We sought to identify challenges that limit access to drinking water; opportunities, including promising practices, to increase drinking water availability and consumption; and future research, policy efforts, and funding needed in this area.